Crafts for accessorising that look - "Blake, Susannah" (Wayland Sussex, 2012)
This is a craft series with a twist. Learn how to makeover your room, revamp your wardrobe, make your own natural beauty products and style your accessories while considering the environment and taking steps to make your own change with your eco-style!